Design And Development of a Solar Tracking System for the UPM Solar Collector - Ahmed, Khalid Osman Daffallah (1999)
In solar energy system, sun tracking can significantly improve the efficiency of any solar array. Solar trackers periodically update the orientations of devices such as reflectors, solar panels or equipment to the actual position of the sun. From these points of view, we designed and developed a tracking system for the UPM solar collector. The system uses a software called Work-Bench in association with two data acquisition and control cards. The UPM solar collector uses two modes of tracking, passive and active tracks. The switch from active to passive is done automatically by comparing the irradiation to a preset value of 300 Wm-2. A manual tracking is also provided. This is required for initialization, shutdown, maintenance and emergency tasks. For the purpose of tracking, two independent stepper motor shafts are attached to the receiver. For the active tracking, the output voltages from two sun position sensors were used to activate the stepper motors. These two sun sensors convert the light intensity into voltage signals. Then by using the WorkBench software these signals are converted into logic signals to control the movement of the stepper motors. The passive tracking was carried out by utilizing the position angles of the sun. These angles were then resolved into two components for the east west and north south tracking. The WorkBench software was then used to convert these two components into voltages. The voltage was calibrated against a reference voltage produced by potentiometers attached to the motor shafts. The output from the comparison was used to control the movement of the stepper motors. Finally, the accuracy of the system was tested by taking the output resistance from a light dependent resistor attached to the receiver. The data indicated that the tracking is satisfactory since the output resistance from the light dependent resistor was approximately constant on a cloudless periods.